Hot Bite`z Cafe / Shahrezza Jeffry... [et al.] - Basri, Khairunisa; Japar, Nur Adibah; Abidin, Siti Farahyyah; Wan Hassan, Wan Anis Syahira; Jeffry, Shahrezza (2014)
HOT BITE'Z is the introduction of sausage bun which serve both Asian and western styles with HALAL permission. It serves the styles of Asian and Western in terms of the sauces. At HOT BITE'Z we have our own bun and sausages that being processed by our own. The chef that we hired has the expertise in serving many kinds of flavour for the sauces, which will have the combination Asian sauce and Western sauces The location of HOT BITE'Z shop lot, is located in 1 Borneo Hyper Mall. It is the most strategic location where the hyper mall is known as the centre of attraction from many people, especially students from UMS and UiTM . There are 5 partners involved in HOT BITE'Z Company. The marketing manager, named, SITI FARAHYYAH BINTI ABIDIN has the expertise in managing the marketing plan. While for our administration part, we have WAN ANIS SYAHIRA BINTI WAN HASSAN that will manage the administration part. We also have our operational manager, named KHAIRUNISA BINTI BASRI. And our financial manager is NUR ADIBAH BINTI JAPAR who will manage the financial account of the company. Last but not least, we have our General Manager, SHAHREZZA BIN JEFFRY that will ensure that the company will run smoothly and success in a long term period.